Understanding interactions between environmental conditions and insect physiology to inform pest management in South Africa - Huisamen, Elizabeth Johanna (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhDConsEcol)--Stellenbosch University, 2021.